2014
DOI: 10.4238/2014.september.5.9
|View full text |Cite
|
Sign up to set email alerts
|

Protection from vascular endothelial dysfunction in acute glycemic load-induced primary hypertension by vitamin C and E

Abstract: ABSTRACT. This study aimed to investigate the influence of acute glycemic load on vascular endothelial function in patients with hypertension and to evaluate the protective effect of vitamins C and E during the acute glycemic phase. We randomly selected 39 hypertensive patients and 21 normal subjects and divided them into 3 groups: 75 g oral glucose (glycemic load group), 75 g glucose + 0.9 g vitamin C (VC group), 75 g glucose + 2 g vitamin C + 0.8 g vitamin E (VC + VE group). Extravascular color Doppler ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Nevertheless, there are some controversial results around this matter and some authors state that vitamin D supplementation have not been demonstrated to improve endothelial function in overweight/obese non-hypertensive individuals 21 . In contrast, a protective role of vitamin E supplementation on vascular endothelial function has been described, especially in hypertensive patients 22 .…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, there are some controversial results around this matter and some authors state that vitamin D supplementation have not been demonstrated to improve endothelial function in overweight/obese non-hypertensive individuals 21 . In contrast, a protective role of vitamin E supplementation on vascular endothelial function has been described, especially in hypertensive patients 22 .…”
Section: Discussionmentioning
confidence: 97%
“…SBP, DBP ⬇, endothelial vasodilation ⬆ and arterial stiffness ⬇ [157,158]. Humans, essential hypertension [176].…”
Section: Vitamin C and Ementioning
confidence: 99%
“…Only randomized trials with a low risk of bias were included in the study. The quality assessment tools used for cross-sectional [12][13][14], cohort [15][16][17][18][19][20][21][22][23][24][25], and case-control studies [26][27][28][29][30] were the Newcastle-Ottawa Quality Assessment Tool for cross-sectional, cohort, and casecontrol studies, respectively. A score of greater than or equal to seven stars during the individual quality assessment, as shown in Table 3, was included in the study.…”
Section: Figure 1: Prisma Flow Diagram Showing Data Extraction Processmentioning
confidence: 99%